Role of Nanotechnology in Forensic Medicine to Solve Medico-legal Case Work in Pakistan - A Review Study - Muhammad Faisal Aslam, Khadeeja Khan, Nadir Ali, Javeria Ghafoor, Muhammad Immran, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Nanotechnology is relatively a new emerging field of Forensic Science and is being used to solve many medico-legal cases all over the world. Some of its use is the most prevalent in biomedical science, material science, biological indicators, food science, Trace Evidence, real-time crime scenes, and terrorist attacks as a nanomaterial to the medico-legal investigations. It is now utilized in the medico-legal casework in Pakistan in Forensic Medicine. Aim: To analyze and compare the forensic value of nanotechnology and methods used to solve the medico-legal investigations relating to nanomaterials in Forensic medicine in Pakistan, Pakistan. Method: This is a review study focusing on the currently available data in research articles all over the world and in Pakistan about the use of nano-material in medico-legal casework for slaving medico-legal investigations in Pakistan. Extensive research is being conducted on the use of nanomaterials. Various analysis methods for nanomaterials, both old and new, have been gathered from previous research and compared. The statistical significance of their use as forensic evidence in criminal investigations and medico-legal cases has been analyzed in the field of Forensic Medicine.